Conservation paradox: strong cultural ties but poor regeneration of chiuri (Diploknema butyracea) in Nepal - Bhattarai, Shreehari; Kunwar, Ripu M.; Shrestha, Arjun K.; Bhatta, Balram (Our Nature, 2025)
Chiuri (Diploknema butyracea), a culturally and economically significant tree in the Nepal Himalayas, plays a vital role as a cultural keystone species. This study examined its regeneration across 90 plots along three elevational gradients: lower (500-800 m), middle (800-1100 m), and upper (1100-1400 m) in western, central, and eastern Nepal. The highest seedling densities occurred in the Upper Central (16 seedlings/ha) and Upper Western (14 seedlings/ha) regions. Regeneration was affected by factors such as disturbance, shade intolerance, thick litter layers, short seed viability, and grazing. Notably, areas with low disturbance and strong traditional conservation practices, especially among the Chepang community, showed better regeneration outcomes. The findings highlight the value of indigenous knowledge in promoting forest health. To ensure the long-term survival of Chiuri, the study recommends establishing seed orchards, promoting public awareness, and launching large-scale plantations. These efforts would enhance both the ecological sustainability and cultural significance of this important Himalayan species.